Evaluation of foliar application of Elusine indica extract on growth, photosynthesis, and osmoprotectant contents in maize under drought stress - Han, Mingzhao; Kasim, Susilawati; Yang, Zhongming; Deng, Xi; Abdullah, Halimatul Sa’adiah; Mohd Shuib, Effyanti; Uddin, Md Kamal (Universiti Putra Malaysia Press, 2024)
To investigate the effects of foliar application of different concentrations of Elusine indica extract (EIE) on growth, photosynthesis, and osmoprotectant contents in maize under drought stress. The weed powder was extracted using methanol, followed by a solid-liquid extraction procedure. Plants were sprayed with three different concentrations of EIE at 1, 3, and 5 g/L and morphological parameters, chlorophyll, relative water content (RWC), soluble sugar, proline, protein, glutathione (GSH), and malondialdehyde (MDA) contents were determined. The results showed that drought stress led to a decline in morphological characteristics, RWC and soluble sugar and increased proline, protein, GSH, and MDA contents. However, foliar application of EIE significantly improved plant height, fresh and dry weight, chlorophyll content, RWC, soluble sugar, and GSH, while the proline level was diminished compared to drought treatment. Soluble sugar showed a significant positive correlation with fresh and dry weight (r = 0.742 and 0.783, p < 0.01) and a strong negative correlation with MDA (r = -0.459, p < 0.05). Therefore, this result indicated that EIE can be used as an inexpensive and environmentally friendly biostimulant to help plants enhance tolerance to drought.